Competitive Strategy Orientation and Market Orientation for Product Innovative Success in Ethiopian Smes - Teshome Bekele Nege; Chalchissa Amentie Kero (MultiTech Publisher, 2024)
SMEs have increased in efficiency on a global scale thanks to innovation and strategic marketing. Small and medium enterprises (SMEs) are essential to economic success in the ever-changing global economy, especially for rising nations like Ethiopia. However, SME faces challenges that has to be addressed by strategic orientations (Dinku & Belay, 2021; Abebe & Tekle, 2022). In SMEs, innovation and product success have been found to be contingent upon the strategic integration of market orientation and competitive strategy orientation (Chalchissa et al., 2017). Consequently, in order for SMEs to maintain competitiveness, promote innovation, and propel growth in a variety of economic and cultural contexts, they must comprehend and put into practice strategic orientations such as market and competitive strategies (Okello & Luttah, 2022). These approaches aren't as common in emerging economies, though, because SMEs' success and inventiveness are essential for generating income and jobs (Okello & Luttah, 2022)